Improving seismic performance of framed structures with steel curved dampers. (1st January 2017) - Hsu, H.-L.; Halim, H.
Highlights: New curved damper design was proposed to improve performance of frame structures. Effective equation for curved damper strength evaluation was proposed. Effect of curved damper geometries on the structural performance was investigated. Important experimental information on the structural performance was presented. Significant performance enhancement was achieved when curved damper was adopted. Abstract: Moment resisting frames possess significant ductility and thus are commonly used in earthquake-resistant designs. However, excessive deformation due to lower stiffness and structural strength limits the applicability of this system. Steel curved dampers are proposed in this study to improve this system's structural performance. The curved dampers were laser-cut from steel plates with the desired geometries and placed at the beam to column regions. The damper behavior is governed by its length and angle between the two ends. A series of cyclic loading tests were performed on steel frames with various curved damper placements to evaluate the curved damper effect on the structural performance. It was found from the test results that the frame strength was higher when the damper angle was smaller. It was also observed from test result comparisons that significant improvements in strength, stiffness and energy dissipation were achieved when the proposed curved dampers were added to the moment resisting frames. Information obtained from this preliminary investigation will be used as data for comparisons in further study of dynamic behavior of multi-story framed structures.